MI-5. Volume 07 [videorecording(DVD)] - McCarthy, Colm, 1973-; Hoar, Peter (Director); Hall, Edward, 1966-; Miller, Sam, 1962 September 28-; Penry-Jones, Rupert, 1970-; Armitage, Richard, 1971-; Firth, Peter, 1953- (British Broadcasting Corp. ; Distributed by BBC Worldwide Americas ; Distributed by Warner Home Video, 2009)
Having spent years in a Russian prison, Lucas North is welcomed back by MI-5 supremo and old friend Harry Pearce, who was instrumental in finally securing his release. Lucas is keen to get back to work straight away and, with Section D's current priority operation having a strong Russian connection, he could well prove invaluable. But, after so many years with only a high ranking Russian spymaster for company, can Lucas's loyalty really be taken for granted?